2020
DOI: 10.1039/c9mh01684h
|View full text |Cite
|
Sign up to set email alerts
|

Designing carbon conductive filament memristor devices for memory and electronic synapse applications

Abstract: Utilizing the instability of the edge atoms of graphene defects, carbon conductive filaments were formed under the regulation of the electric field and the synaptic function was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 68 publications
0
56
0
Order By: Relevance
“…Yan et al have recently reported that electron hopping between sulfur and metal vacancies is the reason for ultra-fast memristive behavior in two-dimensional metal chalcogenide films. 16 , 23 , 52 , 53 The charge hopping is voltage-dependent, which leads to voltage-dependent PPF as observed in Fig. 3 c. We believe that the same is the underlying mechanism behind observing the PPF/PPD in MoS 2 QD systems as well, and has been discussed in detail later on in this work.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Yan et al have recently reported that electron hopping between sulfur and metal vacancies is the reason for ultra-fast memristive behavior in two-dimensional metal chalcogenide films. 16 , 23 , 52 , 53 The charge hopping is voltage-dependent, which leads to voltage-dependent PPF as observed in Fig. 3 c. We believe that the same is the underlying mechanism behind observing the PPF/PPD in MoS 2 QD systems as well, and has been discussed in detail later on in this work.…”
Section: Resultsmentioning
confidence: 53%
“…Yan et al have recently reported that electron hopping between sulfur and metal vacancies is the reason for ultra-fast memristive behavior in two-dimensional metal chalcogenide films. 16,23,52,53 The charge hopping is voltage-dependent, which leads to voltage-dependent PPF as observed in Fig. 3c.…”
Section: Resultsmentioning
confidence: 90%
“…Combined with the I-V curve, we found that the conductance or resistance of the device can be regulated by electrical signals, similar to the change of synaptic weight. This proves that our device has the potential to simulate the synaptic function, learning, and memory behaviors [27][28][29][30][31]. The synapse consists of presynaptic membrane, synaptic space, and postsynaptic membrane.…”
Section: Resultsmentioning
confidence: 63%
“…Because of the gradually change in current–voltage characteristics at both bias polarities of the Gd x O y memristors with H 2 plasma surface modified CSA graphene BEs, as shown in Figure 4a, a superior adoptability of the devices in artificial synapse is expected. [ 41,63,64 ] Consequently, the basic biomimetic characteristics of potentiation, depression, and spike‐timing‐dependent plasticity (STDP) for the Gd x O y memristors with CSA graphene BEs were measured and are presented in Figure . Figure 6a,b shows the potentiation and depression processes of the Gd x O y memristors with a pristine and a 10 min H 2 plasma surface modified CSA graphene BEs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[ 39 ] It has been reported that if MLG with defects or carbon quantum dots were placed between the electrode and RS layer of memristors, the carbon atoms can drift into the RS layer to form carbon conductive filaments. [ 40,41 ] Nevertheless, these studies did not investigate the plasma treatment on graphene electrodes and discuss its influences on RS behaviors by redox reaction mechanism and biomimetic properties as well. As we know, chemical‐vapor‐deposited (CVD) graphene has been extensively used in a variety of fields, but it is too expensive to be applied in semiconductor manufacturing.…”
Section: Introductionmentioning
confidence: 99%